(untitled) (ASEAN Engineering Journal, 2023)
Currently, housing development is actively carried out in Palembang City, especially in sub-districts with vast underutilized land with relatively cheap prices. People’s preferences for private transport for movement may give rise to congestion on the roads leading to the housing estates due to narrow access roads. The Government of Palembang City has laid out a plan for feeder transportation connecting buses and LRTs. Going forward, the procurement and management for this feeder transportation will be handed over to the public (private sector). There needs to be a route plan that is efficient and easy to modify considering the low number of passengers outside of peak hours and the constantly-changing number at every point. The Saving Matrix was studied for its effectiveness in planning fast and efficient routes. The results of the study showed that calculations using the Saving Matrix method are easy to carry out and produces efficient routes.